2021
DOI: 10.3390/macromol1030014
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-oxazoline)-Based Amphiphilic Gradient Copolymers as Nanocarriers for Losartan: Insights into Drug–Polymer Interactions

Abstract: The current study is focused on the development of highly stable drug nanocarriers by encapsulating losartan potassium (LSR) into an amphiphilic biocompatible poly(2-methyl-2-oxazoline)-grad-poly(2-phenyl-2-oxazoline) (PMeOxz72-grad-PPhOxz28) gradient copolymer (GC). Based on dynamic light scattering (DLS), the PMeOxz72-grad-PPhOxz28 (where the subscripts denote %wt composition of the components) GC formed micelles and aggregates of 13 nm and 96 nm in aqueous milieu. The presence of hydrophobic LSR molecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…It has been reported elsewhere in the literature that the nanoparticles formed by the self-assembly of amphiphilic gradient copolymers of 2-methyl-and 2-phenyl-2-oxazoline had three distinct populations that differed in size and intensityweighted size distribution of DLS plots. 19,20,61 These three populations were unimers (size < 10 nm), nanoparticles (size > 10 nm), and large aggregates (size > 100 nm). Among these, the large aggregates were the most prominent in the intensityweighted size distribution plot.…”
Section: Characterization Of Copolymers and Polymericmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported elsewhere in the literature that the nanoparticles formed by the self-assembly of amphiphilic gradient copolymers of 2-methyl-and 2-phenyl-2-oxazoline had three distinct populations that differed in size and intensityweighted size distribution of DLS plots. 19,20,61 These three populations were unimers (size < 10 nm), nanoparticles (size > 10 nm), and large aggregates (size > 100 nm). Among these, the large aggregates were the most prominent in the intensityweighted size distribution plot.…”
Section: Characterization Of Copolymers and Polymericmentioning
confidence: 99%
“…It was concluded that the formation of large aggregates may be related to the gradient structure of the copolymer chains, which allows greater exposure of the hydrophobic segments to the aqueous environment, facilitating the hydrophobic interaction between the nanoparticles. 19,20,61 Previously, we have shown that the nanoparticles formed by the self-assembly of amphiphilic gradient copolymers of 2-ethyl-and 2-(4-dodecyloxyphenyl)-2-oxazoline also exhibit two distinct populations (one with a size >10 nm and another with a size >100 nm) in the intensity-weighted size distribution plot. 21 In the present study, a closer look at the volume-weighted size distribution of the nanoparticles (Figure 3A) also shows a bimodal distribution except for the (EtOx) 88grad-(HexOPhOx) 12 nanoparticles, indicating two distinct populations.…”
Section: Characterization Of Copolymers and Polymericmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous research papers have reported the promising potential of amphiphilic block copoly(2-oxazoline)-based delivery systems for the entrapment of anticancer drugs with an exceptionally high loading capacity and targeted delivery to cancer cells [28][29][30]. Recently, attempts have been made to investigate the potential of amphiphilic gradient copoly(2-oxazoline)s for the formulation of hydrophobic drugs [31][32][33][34]. Poly(2-methyl-2-oxazoline-grad-2-phenyl-2-oxazoline) (PMeOx-grad-PhOx) is the most studied gradient copoly(2-oxazoline) for drug encapsulation, containing 2-methyl-2-oxazoline (MeOx) as a hydrophilic monomer and 2-phenyl-2-oxazoline (PhOx) as a lipophilic monomer.…”
Section: Introductionmentioning
confidence: 99%